1996
DOI: 10.3109/02656739609023531
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of etoposide induced cell killing by hyperthermia can occur without changes in etoposide transport or DNA topoisomerase II activity

Abstract: We investigated the modification of etoposide (i.e. VP-16)-induced cell killing by hyperthermia in a radioresistant human melanoma (Sk-Mel-3) and a human normal (AG1522) cell line. VP-16, a DNA topo II poison, was given as a 1 h exposure at variable doses up to 35 microM; hyperthermia was given either before or following VP-16 treatment. Hyperthermic treatment comprised one of the following: 41 degrees C for 8 h, 42 degrees C for 2 h or 45 degrees C for 15 min. Hyperthermia preceding VP-16 treatment reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Notably, our viability data and the hyperthermia conditions used here are consistent with the published reports showing that hyperthermia protects cells from the cytotoxic effect of topoisomerase inhibitors [ 33 , 34 , 35 , 36 ]. The possibility that hyperthermia reduced the formation of TOPcc was excluded since multiple independent reports have shown that hyperthermia did not reduce the activity of TOP1, TOP2 or the level of TOP1cc and TOP2cc [ 33 , 35 , 36 ]. On the contrary, it has been suggested that hyperthermia induces the formation of stable TOP1cc during early S-phase [ 61 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, our viability data and the hyperthermia conditions used here are consistent with the published reports showing that hyperthermia protects cells from the cytotoxic effect of topoisomerase inhibitors [ 33 , 34 , 35 , 36 ]. The possibility that hyperthermia reduced the formation of TOPcc was excluded since multiple independent reports have shown that hyperthermia did not reduce the activity of TOP1, TOP2 or the level of TOP1cc and TOP2cc [ 33 , 35 , 36 ]. On the contrary, it has been suggested that hyperthermia induces the formation of stable TOP1cc during early S-phase [ 61 ].…”
Section: Resultssupporting
confidence: 91%
“…In contrast to radiation and several chemotherapeutic agents, hyperthermia failed to sensitize cells to topoisomerase (TOP) inhibitors and instead exerted a protective effect. This paradigm remains unexplained [ 33 , 34 , 35 , 36 ]. Topoisomerases remove topological stress by cleaving and resealing DNA strands.…”
Section: Introductionmentioning
confidence: 99%
“…Etoposide differs from almost all other cytostatics in that thermal enhancement of its effect has not been observed [2,4]. Tumour cells were even found to be protected from etoposide by heat [3,5].…”
Section: Discussionmentioning
confidence: 98%
“…Enhancement of the cytotoxicity of anticancer drugs has been shown in various in vitro and in vivo models, particularly for alkylants [1]. For etoposide, this effect could never be demonstrated [2]. Some data show even a protective effect of heat against etoposide toxicity [3].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that cDDP can suppress the accumulation of heat shock protein HSP-72 as reported by Matsumoto et al indicate that higher treatment efficacy under hyperthermic conditions can also be explained by a drug-related inhibition of cell protection [21]. 13,15,22,24]. These conflicting data show that various tumor cell specific parameters are of great importance for treatment response to hyperthermia.…”
Section: Discussionmentioning
confidence: 99%